Challenges and conceptions of globalization: An investigation into models of global change and their relationship with business practice. Issue 1 (28th January 2014) - Bond, Christopher; J. O'Byrne, Darren
Abstract : Purpose: – This paper, which is conceptual in both nature and approach, builds on a recent contribution to the theorization of "globalization" and seeks to utilise the framework developed therein to help promote a more complex conceptual understanding of the potential implications of how business operates and responds to these challenges in a global environment. The paper aims to discuss these issues. Design/methodology/approach: – The paper draws primarily on a heuristic framework developed by O'Byrne and Hensby that reviews eight models of global change. In this paper, the authors review and give consideration to the relationship between these models and business practice and contend that this relationship is far more complex than the majority of the current literature in the business and management field represents. Within the paper, the authors explore and discuss the dynamics of the eight models of "globalization" and assess the potential implications for business practice of working within these often conflicting and contradictory paradigms of "globalization". As part of this review, the authors consider the strategic implications of "globalization" for business practice and propose a conceptual model with eight strategic options which are aligned to the eight models of global change. Findings: – The paper presents a tentative heuristic framework seeking to align the eight models of global change with strategic options that companies might peruse in response to the global forces for change. The paper concludes by advocating a more integrative and complex understanding of globalization than is currently the case and identifies potential for further research in this area. Originality/value: – The paper develops a conceptual framework for assessing the challenges that processes of globalization present to business. The paper places a particular emphasis on considering the strategic implications of the various models of global change and offers a tentative framework for further debate and discussion.